Flora introduced and naturalized in Central America - Rojas Sandoval, Julissa (2022)
Successful control and prevention of biological invasions depend on identifying the sources, vectors, and pathways that are more likely to originate new invasions. Within this context, updated local and regional checklists of alien species are crucial to design biosecurity protocols and strategies for the management of invasive species. In this study, we compiled a comprehensive dataset of the alien flora of Central America based on newly gathered information from the literature, herbarium records, and consultations with local experts. This new dataset includes information on taxonomy, geographic origin, pathways of introduction, habitats preferences, and economic uses of alien plant species introduced to this region. The alien flora of Central America comprises 1228 species, among which there are 835 (68%) naturalized species and 393 (32%) casuals. The number of aliens varied considerably among countries, with the highest numbers occurring in Costa Rica (957 species) and the lowest in Belize (226 species). Alien species can be sourced to all continents and are dominated by herbs, trees, and shrubs. Most species (60%) were introduced intentionally as ornamentals. Alien species have successfully established and are spreading across all major habitat types in the region, and this may have significant long-term implications for the conservation of native biodiversity but also within the socio-economic context of this region.